The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1002/mpo.2950110416
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine arabinoside induced liver damage: Histopathologic demonstration

Abstract: Two patients with acute leukemia developed abnormal liver function tests after the administration of cytosine arabinoside. Other possible causes for such abnormalities were not likely. In both patients a close chronologic relationship between the administration of the drug and the appearance of the laboratory abnormalities was noted. The liver damage was also documented by biopsy. To our knowledge this is the first time that the hepatotoxic effects of cytosine arabinoside are histologically demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…the obtained results came in agreement with that obtained by Herzig et al (1983), who studied cytosine arabinoside therapy for refractory leukemia (transient elevations in transaminase, alkaline phosphatase, or bilirubin) was frequently observed. Another similar result was obtained by Pizzuto et al (1983) who, reported that cytosine arabinoside induced liver damage. Two patients with acute leukemia developed abnormal liver function tests after the administration of cytosine.…”
Section: Discussionsupporting
confidence: 84%
“…the obtained results came in agreement with that obtained by Herzig et al (1983), who studied cytosine arabinoside therapy for refractory leukemia (transient elevations in transaminase, alkaline phosphatase, or bilirubin) was frequently observed. Another similar result was obtained by Pizzuto et al (1983) who, reported that cytosine arabinoside induced liver damage. Two patients with acute leukemia developed abnormal liver function tests after the administration of cytosine.…”
Section: Discussionsupporting
confidence: 84%
“… 10 Nevertheless, there are reports of severe drug-induced hepatic cholestasis related to cytarabine therapy. 11 …”
Section: Specific Chemotherapymentioning
confidence: 99%
“…Free plasma concentrations of 17AAG in patients have been noted to be in the low 1 to 5 Amol/L range for up to 12 h after drug infusion, which is significantly higher than the required concentration of drug to inhibit HSP90 function (19). Many established therapeutic agents have also been shown to have varying toxicities in the liver, both killing hepatocytes and causing cholestasis, including 1-h-D-arabinofuranosylcytosine (20), arsenic trioxide (21), and platinum drugs (22).…”
Section: Introductionmentioning
confidence: 99%